2020
DOI: 10.1101/2020.09.02.280180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of a regulatory myeloid program in bacterial sepsis and severe COVID-19

Abstract: A recent estimate suggests that one in five deaths globally are associated with sepsis1. To date, no targeted treatment is available for this syndrome, likely due to substantial patient heterogeneity2,3 and our lack of insight into sepsis immunopathology4. These issues are highlighted by the current COVID-19 pandemic, wherein many clinical manifestations of severe SARS-CoV-2 infection parallel bacterial sepsis5–8. We previously reported an expanded CD14+ monocyte state, MS1, in patients with bacterial sepsis o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
(76 reference statements)
5
13
0
Order By: Relevance
“…Several factors are involved in the expansion of M-MDSCs, including IL-6 and GM-CSF (14). Furthermore, IL-6 and IL-10 have been shown to be essential in inducing emergency myelopoiesis resulting in expansion of an M-MDSC-like cell subset in severe COVID-19 (47). In line with previous studies (12,33), we demonstrated a relationship between IL-6 and COVID-19 disease severity.…”
Section: Discussionsupporting
confidence: 89%
“…Several factors are involved in the expansion of M-MDSCs, including IL-6 and GM-CSF (14). Furthermore, IL-6 and IL-10 have been shown to be essential in inducing emergency myelopoiesis resulting in expansion of an M-MDSC-like cell subset in severe COVID-19 (47). In line with previous studies (12,33), we demonstrated a relationship between IL-6 and COVID-19 disease severity.…”
Section: Discussionsupporting
confidence: 89%
“…36,38,55 Many severity-associated proteins were also associated with the nuclear factor kB (NF-kB) pathway, showing substantial overlap with published bronchial and nasopharyngeal cells collected from patients, 38,55 genes induced by TNF-a in monocytes in vitro, 56 and a TNF-a pathway signature observed by scRNA-seq in COVID-19 severity-associated monocytes. 17,57 Few severity-associated proteins were part of the type I IFN response, in agreement with published data 4,7 and with the association of COVID-19 severity with genetic variants that weaken IFN-related viral sensing. 58 Our proteomic analysis of a large cohort of COVID-19 patients reveals COVID-19 severity-and mortality-associated pathways that may serve as potential therapeutic targets and provide the basis for diagnostics to stratify highrisk patients for tailored therapies and earlier interventions.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that besides the early increase in CD169 + monocytes in all COVID-19 patients associated with T cell dysfunctions, the immunological response to SARS-CoV-2 infection features multiple alterations of monocytic subsets reflecting the severity of the disease. Consistent with these data, it was shown that CD14 + HLA-DR low cells were increased in critical COVID-19 patients, 21,26,[56][57][58] while CD14 low CD16 + monocytes, able to migrate to the lung, were correlated with the length of stay in the ICU. 15,23,59 Our study correlates the accumulation of nonclassical monocytes and M-MDSCs occurring during the first days of ICU to adverse events.…”
Section: Discussionsupporting
confidence: 71%